Characterization of green-synthesized carbon quantum dots from spent coffee grounds for EDLC electrode applications - Grishika Arora; Nuur Syahidah Sabran; Chiam-Wen Liew; Chai Yan Ng; Foo Wah Low; Pramod K. Singh; Hieng Kiat Jun (Chemical Physics Impact)
This study investigates the green synthesis of carbon quantum dots (CQDs) from spent coffee grounds using a hydrothermal method, offering an eco-friendly, cost-effective, and straightforward approach to nanomaterial production. The synthesized CQDs, with particle sizes ranging from 1.6 to 4.4 nm, exhibited notable fluorescence, achieving quantum yields of 37.0 %, 54.3 %, and 63.3 % depending on the coffee source. Characterization technique, including XRD, FTIR, SEM, TEM, and BET, confirmed their structural suitability of these CQDs for energy storage applications. Their electrochemical performance was evaluated through cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), and electrochemical impedance spectroscopy (EIS). Among the CQDs tested, those derived from spent Liberica coffee ground (medium roasted) demonstrated superior performance, with a discharging specific capacitance of 97.5 F/g, an energy density of 4.3 Wh/kg, and a power density of 130.6 W/kg at a current density of 0.5 A/g. Additionally, they exhibited acceptable internal resistance (Ra = 0.01 kΩ and Rab = 16.9 kΩ), indicating favourable charge transfer characteristics. These results underscore the enhanced energy storage potential of CQDs derived from spent coffee grounds. The findings not only highlight the excellent electrochemical performance but also support the viability of biomass waste as a valuable resource for advanced energy storage applications, promoting sustainable, eco-friendly technologies.